The Prevalence of Clinical Features in Patients with Aarskog–Scott Syndrome and Assessment of Genotype-Phenotype Correlation: A Systematic Review - Victor Zanetti Drumond; Lucas Sousa Salgado; Camila Sousa Salgado; Vitor Augusto de Lima Oliveira; Eliene Magda de Assis; Michel Campos Ribeiro; Analina Furtado Valadão; Alfredo Orrico (Genetics Research, 2021)
Aarskog–Scott syndrome is a genetically and clinically heterogeneous rare condition caused by a pathogenic variant in the FGD1 gene. A systematic review was carried out to analyse the prevalence of clinical manifestations found in patients, as well as to evaluate the genotype-phenotype correlation. The results obtained show that clinical findings of the craniofacial, orthopaedic, and genitourinary tract correspond to the highest scores of prevalence. The authors reclassified the primary, secondary, and additional criteria based on their prevalence. Furthermore, it was possible to observe, in accordance with previous reports, that the reported phenotypes do not present a direct relation to the underlying genotypes.